When Dark Personality Gets Darker: The Intersection of Injustice, Moral Disengagement, and Unethical Decision Making - Justin Travis; Catherine A. Neale; Samuel J. Wilgus (Merits)
Despite advances in understanding the factors that predict unethical behaviors such as counterproductive workplace behavior (CWB), there is still substantial variance left unexplained in the occurrence of unethical behavior. Recent research has examined how unethical behavior may change beyond initially reported levels due to the gradual erosion of ethicality via justification processes such as moral disengagement. The present study extends this research by examining the role of personality in determining the extent to which individuals make subsequent unethical decisions at greater or lower levels beyond their initial levels. Studies 1 and 2 used an experimental design that presents half of participants with an opportunity to practice moral disengagement by allowing participants to justify their actions. Results in study 1 demonstrate that individuals with high levels of dark personality traits tend to increase their level of unethical decision making when given the chance to justify their actions, whereas those with low levels of dark personality become less unethical. Study 2 examines the extent to which the mediating role of perceived justice changes when participants are given an opportunity to justify their actions. Results from study 2 show the effects of justice as a mediating mechanism are significantly diminished when the justification manipulation is present. Implications emphasize the need to use both selection and development interventions in organizations to reduce gradual decreases in ethicality as well as reduced reliance on cross-sectional research to study a phenomenon that can change as unethical behavior is justified.